Plasma cell purification from murine bone marrow using a two-step isolation approach - Minges Wols, Heather A. (2007)
Interest in plasma cells has increased greatly in the past decade. While several studies have examined the longevity and transcriptional control of antibody secreting cells in vivo, few studies have examined freshly isolated plasma cells ex vivo. Studies of primary plasma cells have been limited primarily due to the difficulty of isolating the large numbers of plasma cells necessary for experiments. In this protocol, plasma cells are purified from murine bone marrow in approximately 5 hours, following a two-step isolation method utilizing column enrichment and FACS-sorting based on CD138 (Syndecan-1) surface expression.